AI-ARC Baltic Demo: Detecting Illegal Activities at Sea - Svenson, Pontus; Holst, Anders; Wallberg, Anders; Nevalainen, Paavo; Farahnakian, Farshad; Álamo, Alfonso; Germinara, Vincenzo; Schweizer, Daniel; Leicht, Matthis; Anneken, Mathias; Hoppe, Adrian H.; Karalis, Aristeidis; et al. (United States, 2025)
We describe the AI-ARC (Artificial Intelligence-based Virtual Control Room for the Arctic) system, which aims to enhance maritime domain awareness and surveillance. The system is micro-service based and fuses data from various sources, utilizing AI-driven micro-services and an advanced visualization platform to increase the situation awareness of maritime surveillance operators. The results of the Baltic sea demonstration, aiding in the detection of illegal activities, environmental protection, are presented. The system was evaluated using historical data from real criminal incidents. The resultsshow that the AI-ARC approach could help increase the situation awareness of law enforcement operators.
2024 27th International Conference on Information Fusion (FUSION)